2002
DOI: 10.1021/jp0134749
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction of Conjugated Molecular SAMs Studied by Conductive Atomic Force Microscopy

Abstract: The electrical conduction of self-assembled monolayers (SAMs) made from conjugated molecules was measured using conductive atomic force microscopy (AFM), with a focus on the molecular structural effect on the electrical conduction. For phenylene oligomer SAMs, resistances through the monolayers increased exponentially with increases in molecular length and the decay constants of transconductance β were ca. 0.35 to 0.5 Å-1. Using an insertion technique into insulative alkanethiol SAMs, we successfully obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
171
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(185 citation statements)
references
References 41 publications
(157 reference statements)
13
171
0
1
Order By: Relevance
“…Previous research has shown that π-π intermolecular interactions have a strong impact on the conductivity of organic films [12][13][14][15]19 . Theoretical calculations also indicate that a well-ordered structure should decrease the tunneling resistance across molecules by the better spatial overlap of the HOMO and LUMO molecular orbitals 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that π-π intermolecular interactions have a strong impact on the conductivity of organic films [12][13][14][15]19 . Theoretical calculations also indicate that a well-ordered structure should decrease the tunneling resistance across molecules by the better spatial overlap of the HOMO and LUMO molecular orbitals 15 .…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies on various -conjugated molecules have been performed. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The molecules, with delocalized electrons due to sp 2 hybridized carbon atoms, exhibit a smaller energy gap between the highest occupied molecular orbital ͑HOMO͒ and the lowest unoccupied molecular orbital ͑LUMO͒. For -conjugated molecules longer than ϳ3 nm hopping conduction was observed.…”
Section: Electrical Characteristics Of Conjugated Self-assembled Monomentioning
confidence: 99%
“…Nevertheless, the ␤-values found for the phenylenes are lower than reported in literature using single molecules as well as SAMs, i.e., ␤ = 0.35-0.61 Å −1 . 3,[5][6][7][8]10 To address the relative low values of ␤, it is interesting to make a comparison with theoretical predictions. Calculations using different formalisms resulted in ␤ = 0.17-0.51 Å −1 .…”
Section: Electrical Characteristics Of Conjugated Self-assembled Monomentioning
confidence: 99%
“…), [4,17,18] and carotenoid polyenes (0.22 AE 0.04 À1 ). [19] Small b values (b < 0.1 À1 ) [20][21][22] have also been reported for highly conjugated and low-band-gap systems, such as the alkyne-bridged complex with a b value of 0.04 AE 0.02 À1 , [20] extremely low attenuation of 0.04 AE 0.006 À1 for oligo-zinc porphyrin, [21,22] and 0.06 AE 0.03 À1 for oligoyne series.…”
mentioning
confidence: 99%